EXPLORING ADOLESCENT RESILIENCY DURING RECENT PARENTAL DEPLOYMENT - Buck, Joyce M (East Carolina University, 2017)
Background: Military adolescents experience more behavioral risk factors, such as depression and suicidal ideation than civilian adolescents and often have difficulty adjusting to the many changes inherent in the lives of military-connected children. Eighty percent of military-connected children attend civilian public-schools and often have difficulty adjusting to new school environments. Furthermore, military culture is often misunderstood by non-military school personnel. Objectives: Explore the environment of adolescents who attend public schools and its relationship to effective coping or resilience with regard to parental deployment. Methods: Individual interviews with adolescents and school staff were conducted in a high school in a rural county of eastern NC. Limited participant observation and examination of relevant documents were utilized as well. The county is the home of a major US military base. All the student participants attended public school and have experienced at least one recent parental deployment. Conventional content analysis was used to interpret the data. Results: The military-connected adolescents in schools (MCAS) in this study demonstrated resilience in terms of the constant changes they experience as result of being a MCAS. They express a gamut of emotions in dealing with everyday life among the turmoil of adolescence and the challenges of having one or more parents who are active in the military. They strive to be normal kids who do normal things with normal people. They immerse themselves in many activities in and around the public-school environment to live their lives to the fullest. Discussion: This study suggests that nursing practice can be enhanced when the assessment includes status of parental deployment. In the school setting, the school nurse should be aware of when deployment occurs and how deployment influences adolescent feelings and emotions. A better understanding of this unique population will further the Healthy People 2020 goal to improve the development, health, safety, and well-being of military-connected adolescents.
Keywords: Parental Deployment; Military Connected Children; Military Connected Adolescence; Parents; Resilience, Psychological; Adolescent